Western Ontario and McMaster Universities (WOMAC) Osteoarthritis Index as an Assessment Tool to Indicate Total Knee Arthroplasty in Patients with Primary Knee Osteoarthritis - Ab Rahman, S; Narhari, P; Sharifudin, MA; Shokri, AA (IIUM Medical Journal Malaysia, 2020)
Introduction: The WOMAC questionnaire is used extensively in the assessment of knee osteoarthritis but not as an indicator of total knee arthroplasty (TKA). We aimed to assess if the WOMAC score can be used as an assessment tool to indicate TKA in primary knee osteoarthritis. Materials and Methods: Patients with primary knee osteoarthritis Kellgren and Lawrence grades 3 or 4 were assessed separately by either one of two arthroplasty surgeons for indications to undergo TKA and evaluated using the WOMAC score. Patients who had received any form of intra-articular knee injection within six months before assessment were excluded. Patients were divided into two groups; indicated for TKA, and for non-surgical treatment. The mean WOMAC score of patients from both groups was compared using Independent t-test. The accuracy at different cut-off points in the score indicated for TKA was determined using the receiver operating characteristic (ROC) curve plotted on sensitivity and 1-specificity graph. Results: The study included 74 patients with a mean age of 62.5 years (SD=8.26). There was a significant difference in the total WOMAC score (p<0.001) and its components between patients of the two groups. At the cut-off point of 30, the specificity and sensitivity of the score indicated for TKA was 91.18% and 95.00% respectively. The positive predictive value was 93.24%. Conclusion: We recommend all primary knee osteoarthritis Kellgren and Lawrence grades 3 or 4 with a score of 30 and above should be referred to an arthroplasty surgeon for the possibility of requiring TKA.